Profile of the Phenolic Compounds of Rosa rugosa Petals - Andrzej Cendrowski; Iwona Ścibisz; Marta Mitek; Marek Kieliszek; Joanna Kolniak-Ostek (Journal of Food Quality)
Rosa rugosa petals are a rich source of phenolic compounds, which determined their antioxidant properties. The aim of this study was to determine the polyphenolic composition of not processed petals of Rosa rugosa collected from the commodity crops and to determine the variability of the contained therein polyphenols between harvesting seasons. Twenty polyphenols were identified by UPLC-ESI-MS. The main fraction of polyphenols was ellagitannins, which are 69 to 74% of the total polyphenols of the petals. In the petals of Rosa rugosa, four anthocyanins have been identified: cyanidin 3,5-di-O-glucoside, peonidin 3-O-sophoroside, peonidin 3,5-di-O-glucoside, and peonidin 3-O-glucoside, of which the predominant peonidin 3,5-di-O-glucoside represented approx. 85% of all the determined anthocyanin compounds. It was found that the petals of Rosa rugosa are a valuable source of bioactive compounds and can be considered as a healthy valuable resource.